The Effect of Compound Skill Exercises On The Development of Dribbling And Trapping Motor Speed In Young Soccer Players Aged 14 – 16 Years Old - Mousa, Mohammed (Journal of Physical Education, 2017)
Compound exercise are considered as one of the most important exercise of the game that work on developing the skillful side of soccer players. However, the motor response speed is considered one of the motor skills that any sport activity should have. So, it`s normal that this response ranges from one activity to another according to the planning and skillful requirements in every day activity. The problem of the present study is attributed to the fact that motor speed is slow when performing the skills of scoring and passing. The aim of the present study is to put special compound skillful exercises to develop the motor speed of dribbling and trapping for the Juniors aged (14-16 years old). Therefore it is hypothesized that there are statistical differences between the pre and posttests in the control and experimental groups. The subjects were (16) players from "Ammo Baba football school for juniors" whose ages ranged from 14-16 years. The researcher conducted motor response speed tests, dribbling and trapping. The researcher has discussed the results in chapter four. One of the results is the effectiveness of the special compound exercises developing the motor speed of dribbling and trapping for the subjects of the experimental group. The researcher recommends paying attention to preparation stage by focusing on the importance of the skill and physical preparation in terms of the training approach